Preparations for married life of engaged Filipino couples - Cortes, Pamela Ruth B.; Tongson, Excelsa C. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
Engagement is the stage where individuals in a relationship both agree to commit themselves to marriage. This qualitative study seeks to describe the experiences of engaged Filipino couples, focusing on their preparations for married life and how they went about these preparations. Through purposeful sampling, 10 fiances and 10 fiancees from Metro Manila, all unrelated, participated in in-depth interviews which were analyzed through thematic analysis. Results shows that the stage of engagement covers several preparations from planning the wedding, enjoying the last moments of singlehood with immediate family members and friends while learning to become independent from them, and shifting one's focus towards the future of their family by discussing their roles and expectations of each other, financial management, career direction, children, and residence as well as family background, honeymoon plans, and intimacy. These preparations were influenced by different people significant to the couples, experiences, and even external factors such as society, culture, and religion. In addition, discussions on these preparations began even before engagement and they became clearer, more serious, specific, and concrete as their relationships progressed. Future studies are recommended to incorporate a larger sample size as well as other types of engaged couples living in rural areas and specific religious sects and those who are remarrying and have cohabited before getting married. Furthermore, the direct impact on two specific areas of preparations for married life such as financial management and residential set-up can be also explored.
Thesis Classification: F
Thesis
Includes bibliographical references and appendices.
Keywords: Betrothal